1998
DOI: 10.1002/(sici)1097-0215(19981218)79:6<565::aid-ijc3>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expression of the lipocalin NGAL in primary breast cancers

Abstract: We have previously shown that neu oncogene-initiated rat mammary carcinomas uniquely over-express neu-related lipocalin (NRL), a member of the calycin protein superfamily. Here, we characterize the putative human homolog of NRL, neutrophil gelatinase-associated lipocalin (NGAL). ngal gene expression was found at moderate levels in only 2 of 17 human tissues examined, breast and lung. When breast cancers were examined for NGAL mRNA and protein levels, they were found to exhibit heterogeneous expression. NGAL le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…Blotted membranes were blocked in 5% BSA and subsequently exposed to primary antibodies specific for NGAL, diluted (1 : 1000) in PBS. The rabbit polyclonal anti-NGAL antibody, generously provided by Dr Gould (University of Wisconsin, Madison, WI), was raised against recombinant NGAL protein (Stoesz et al, 1998). After incubation with the appropriate secondary antibody, the membranes were treated with ECL reagent (Amersham Biosciences, Piscataway, NJ, USA) and exposed to autoradiographic films.…”
Section: Cell Lysates and Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Blotted membranes were blocked in 5% BSA and subsequently exposed to primary antibodies specific for NGAL, diluted (1 : 1000) in PBS. The rabbit polyclonal anti-NGAL antibody, generously provided by Dr Gould (University of Wisconsin, Madison, WI), was raised against recombinant NGAL protein (Stoesz et al, 1998). After incubation with the appropriate secondary antibody, the membranes were treated with ECL reagent (Amersham Biosciences, Piscataway, NJ, USA) and exposed to autoradiographic films.…”
Section: Cell Lysates and Western Blotmentioning
confidence: 99%
“…Immunohistochemistry experiments were performed on 39 formalin-fixed tissue samples representing normal (n ¼ 8), pancreatitis (n ¼ 4), and pancreatic adenocarcinoma (n ¼ 27), using the rabbit anti-NGAL polyclonal antibody (Stoesz et al, 1998). The results are summarised in the Tables 1 -3.…”
Section: Immunohistochemistry Of Pancreatic Tumoursmentioning
confidence: 99%
“…A potential function for LCN2 in the migratory capacity of colon cells (Playford et al, 2006) and tissue invasion by leukemia cells (Leng et al, 2008) has also been documented. The LCN2 gene is specifically downregulated in estrogen receptor a positive (ERA þ ) breast cancer patients (Stoesz et al, 1998) and has been reported as a predictor of breast cancer progression (Bauer et al, 2008;Provatopoulou et al, 2009). It has been clearly shown that expression of ERA is associated with more differentiated, less invasive tumors.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 NGAL mRNA and protein have been found to be overexpressed in a broad spectrum of cancers, including breast, ovarian, pancreatic, colorectal, lung, urinary bladder, and hepatic tumors. [5][6][7][8][9][10] Moreover, NGAL levels are elevated in the urine of breast and bladder cancer patients. 5,8 Thus, it is hypothesized that NGAL may play a role in cancer pathophysiology.…”
mentioning
confidence: 99%